Energy Dependence of Total Cross Section for Scattering of Helium Atoms from Isolated Atomic Steps (Journal of Bangladesh Academy of Sciences, 2010)
The scattering of helium atoms from growing metal. surfaces is dominated by the interactionbetween incident atoms and isolated surface steps. Understanding the process has been constrainedby the lack of both a realistic interaction potential and a satisfactory method for treating thescattering from a defect, which, because of the height difference of the adjoining terraces, extendsto infinity. We have calculated step scattering cross sections for Cu(001) surface. The calculationsmake use of realistic potentials that reproduce the scattering from low index planes and are createdfrom non-spherical, pairwise repulsive and attractive terms. The step scattering is isolated from thatof adjoining terraces using the linearity of summation of scattering amplitudes in the singlescattering regime. The results for equivalent step and terrace-site potentials give a total crosssection significantly less than the experimental value. The total cross section increases with heliumbeam energy, contrary to the expectations that it is dominated by scattering from the attractive partof the potential. The present work confirms the prediction of our previous study that not the Vander Waals interaction but the hard wall of the scattering potential dominates the step scattering.Key words: Energy dependence; Scattering; Helium atoms; Atomic stepsDOI: 10.3329/jbas.v34i1.5489Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 23-31, 2010